Building Positive Word-Of-Mouth Reputation: Examining The Mediating Role Of Customer Satisfaction In The Relationship Between Service Quality And Customer Value - Sukaris Sukaris (Jurnal Manajerial, 2026)
Background- Intensifying competition among private universities institutions in Indonesia has increased the need to identify strategic factors that drive positive word of mouth (WOM) among students. Aim- This study aims to examine the effects of service quality on customer value and student satisfaction, as well as to test the mediating role of student satisfaction in the relationship between service quality, customer value, and WOM. Design /methodology /approach- This study uses a quantitative approach with a survey method on 200 active students at one of the PTS in Gresik Regency. Data were analyzed using multiple linear regression to examine the relationships among the study variables. Findings- The results indicate that service quality has a positive and significant effect on customer value and student satisfaction. In addition, customer value significantly influences student satisfaction. The key finding reveals that student satisfaction plays a mediating role in strengthening the effects of service quality and customer value on positive WOM. Research implications- This study contributes empirical evidence to the service marketing and private universities literature and offers practical implications for private universities administrators in developing sustainable service quality and customer value strategies. Research limitations- This study used a cross-sectional design and one research location, so it was not able to capture changes in student perceptions longitudinally and limited the generalizability of the findings to other private universities contexts.